2015
DOI: 10.1017/s1352465815000508
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Emotion Regulation as a Mediator between Posttraumatic Stress Symptoms and Hypomanic Personality within a Non-Clinical Population

Abstract: The relationship between traumatic events and an increased prevalence of bipolar disorder remains poorly understood. Further research should explore rumination as a potential target for treatment within those suffering from both posttraumatic stress and bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Particular credence should be given to the strength of the evidence provided by this study, given the triangulation of data from experimental paradigms and behavioral self‐report of the use of these strategies. Mania risk was also positively associated with self‐reported tendencies towards using reappraisal in a further study (medium effect; Steel, ). Two familial risk studies also assessed use of reappraisal, with both finding no difference between participants with bipolar disorder and unaffected relatives (Green et al, ; Kanske et al, ); one study suggested that unaffected relatives report less positive reappraisal than controls (small effect; Kanske et al, ), while the other, found no difference (Green et al, ).…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…Particular credence should be given to the strength of the evidence provided by this study, given the triangulation of data from experimental paradigms and behavioral self‐report of the use of these strategies. Mania risk was also positively associated with self‐reported tendencies towards using reappraisal in a further study (medium effect; Steel, ). Two familial risk studies also assessed use of reappraisal, with both finding no difference between participants with bipolar disorder and unaffected relatives (Green et al, ; Kanske et al, ); one study suggested that unaffected relatives report less positive reappraisal than controls (small effect; Kanske et al, ), while the other, found no difference (Green et al, ).…”
Section: Resultsmentioning
confidence: 71%
“…However, familial risk was associated with this response to negative affect, with two studies suggesting that those with diagnosed bipolar disorder reported more self‐blame than unaffected relatives (medium and large effects; Green et al, ; Kanske et al, ), and unaffected relatives reported more than controls (medium effect; Green et al, ). Blaming others was not related to behavioral (Steel, ) or familial (Green et al, ) measures of risk.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations